Reflective practice in action: an account of psychotherapists' experiences in group-work training. Issue 6 (2nd November 2021) - Grover, Naveen; Lakhani, Sheetal; Emran, Ashti
ABSTRACT: The importance of reflective practice in psychotherapy has long been acknowledged. However, there is a paucity of work that elucidates the process of reflection in the context of therapist development. The current study employs reflexive action research for a supervised group-work in a tertiary mental health hospital carried out by two trainee therapists. Group-work intervention was chosen because it was viewed as a cost-effective method given the client-clinician ratio. It also provided a richer context to boost reflective practices in various interactions- with the participants, the supervisor and the co-facilitator. Reflective notes and discussions among trainees, supervisor, as well as verbatim feedback from clients were the sources of information. The paper describes this process of reflection as well as the critical events in the process that posed a challenge for the therapists and opportunities for reflection in these interactions during the course of therapy. The paper, with its reflective stance, has implications for promoting and documenting reflective practice in psychotherapy training using different methods and modalities.